TINGKAT KEBUGARAN JASMANI DAN TEKNIK DASAR SEPAK BOLA DI SMP 2 PONTIANAK - Purnairawan, Bayu Agus; Atiq, Ahmad; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
In today"™s, sports can be a place to make a person healthy in both physical and spiritual places, and not only adults do it but even children can do it, but sports are also for the development of a level of athlete"™s ability.as well as for fan. As for the purpose of this study to find out the tile of fitness and basic soccer techniques at the first high school 2 pontianak, as for the methot used in this study is a in the study the data-analysis techniques used in descriptive stastistics that are intended to collect data, presend data, and determine values, the results are divided into 5 categories to determine each category interval. As for the category taken in which it is good, good sufficient, less, and less. As for the results of this study of 30 samples involved in data retrieval as a very good category there are 13 athletes ata 43% percentage. Good category is there are athletes at 23% presentation, there are 8 athletes at 26 percent presentation, and there are less than 2 at 6%. The conclusion from the researchers who were able to extras is that the very good category is that there are 13 athletes at a 43% percentage, good category there are athletes at 23% presentation, that there are 8 at.